Pemodelan 3D Bidang Gelincir Tanah Longsor Menggunakan Metode Geolistrik di Bukit Nobita Padang - Arif, M.; Pujiastuti, Dwi; Pohan, Ahmad Fauzi (Jurnal Fisika Unand, 2024)
The surface of rupture investigation has been conducted at Nobita Hill, Kampung Jua, Lubuk Begalung, Padang City using the 3-dimensional resistivity geoelectric method in Wenner configuration. The research was conducted in a hilly area with a slope of up to 40Âº. Data was collected on three tracks with variations in length lengths of 120 and 240 m. The electrode spacing is 6, 12, 18, and 24 m for current and potential electrodes. Data processing was carried out using Res2dinv software to display a 2-dimensional image of the subsurface layer based on the resistivity values measured in the field. The results of 2-dimensional image processing were then modeled in 3 dimensions using Voxler software. Data interpretation of the results obtained by Track 1 has a resistivity value of 1170-2028 Î©m at a depth of 4.5-19.1m. Track 2 has a resistivity value of 1052-1768 Î©m with a depth of 4.5-19.1 m. Track 3 has a resistivity value of 1492-2937 Î©m at a depth of 1.5-19.1 m. The direction of the sliding plane of Tracks 1 and 2 is to the northwest, while track 3 is to the northeast. The results showed that the sliding plane on each track is granite.